(untitled) (REMUNOM, 2024)
In this article, a systematic review of available studies on the impacts of parental alienation on children’s mental and emotional health is presented. Parental alienation is described as a complex and harmful phenomenon, in which one parent exerts a negative influence on the child, compromising their relationship with the other parent. The research analyzed a wide variety of studies, both quantitative and qualitative, published over the last decade. The results showed that parental alienation is correlated with several unfavorable consequences for children, such as emotional problems (such as anxiety, depression and low self-esteem), as well as interpersonal and academic difficulties. Additionally, it was found that such effects can last into adulthood, negatively impacting long-term well-being. The importance of dealing with parental alienation proactively is highlighted by the findings. Targeted interventions are crucial to fostering healthy bonds between parents and children, encompassing awareness strategies, emotional support and parental guidance. Furthermore, the collaboration of mental health professionals and the judicial system is essential to safeguard the best interests of the child. In summary, the study highlights the pressing need for a more comprehensive and collaborative approach to addressing parental alienation, aiming to ensure children’s well-being and promote healthy family relationships.